2010
DOI: 10.1007/978-90-481-9078-2_1
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxins: Lipopolysaccharides of Gram-Negative Bacteria

Abstract: Endotoxin refers lipopolysaccharide that constitutes the outer leaflet of the outer membrane of most Gram-negative bacteria. Lipopolysaccharide is comprised of a hydrophilic polysaccharide and a hydrophobic component known as lipid A which is responsible for the major bioactivity of endotoxin. Lipopolysaccharide can be recognized by immune cells as a pathogen-associated molecule through Toll-like receptor 4. Most enzymes and genes related to the biosynthesis and export of lipopolysaccharide have been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 123 publications
3
108
0
4
Order By: Relevance
“…However, LPS can also elicit an host reaction because it is a major mediator of pathologic processes (4). The strength of the innate immune response to LPS can be modulated by its chemical structure; specifically, a fine tuning of the lipid A structure can significantly affect the immunostimulatory properties of the whole LPS molecule (5,6). There is a strong correlation between the number of acyl chains of lipid A and the immunological response via the TLR4 pathway.…”
mentioning
confidence: 99%
“…However, LPS can also elicit an host reaction because it is a major mediator of pathologic processes (4). The strength of the innate immune response to LPS can be modulated by its chemical structure; specifically, a fine tuning of the lipid A structure can significantly affect the immunostimulatory properties of the whole LPS molecule (5,6). There is a strong correlation between the number of acyl chains of lipid A and the immunological response via the TLR4 pathway.…”
mentioning
confidence: 99%
“…In the present study, we found higher concentrations of LPS (C2 mg/ml) were toxic to the animal. Recent evidence suggested that P. aeruginosa LPS displayed heterogeneity in nature between the strains and was able to change its own LPS compositions during host interactions (Bryant et al 2010;Wang and Quinn 2010). The present study revealed that PAO1 had dramatically changed its own LPS at the polysaccharide (1,200-900 cm -1 ) and fatty acid (3,000-2,800 cm -1 ) regions during the host contact, which was further confirmed by FTIR, PCA and also by X-Ray diffraction studies.…”
Section: Discussionmentioning
confidence: 99%
“…1, the organization of the DUF1239-related gene cluster is mostly conserved in the analysed bacteria, except for the absence of RSc0412 (kdsC/ybrI) in a few bacteria. In E. coli, the five genes included in this cluster are involved in LPS biosynthesis (KdsD, KdsC) or LPS transport (LptC, LptB, LptA) (Wang & Quinn, 2010) and are organized into three operons ( Fig. 1; Sperandeo et al, 2007).…”
Section: Sequence Analysis and Organization Of Duf1239-related Gene Cmentioning
confidence: 99%
“…Rough (R-)LPS are composed of the hydrophobic membrane-anchored lipid A moiety and the short core oligosaccharide, and the addition of variable O-antigen polysaccharide chain onto R-LPS leads to the formation of the complete structure of smooth (S-)LPS. The synthesis, assembly and transport of LPS components are well studied in Escherichia coli (Raetz & Whitfield, 2002;Wang & Quinn, 2010;Sperandeo et al, 2011). R-LPS are synthesized via a conserved pathway, which involves proteins on the cytoplasmic surface of the inner membrane (IM), then transported by MsbA across the IM where ligation of R-LPS to O-antigen is triggered by WaaL to form S-LPS.…”
Section: Introductionmentioning
confidence: 99%